(untitled) (Ciudades, 2018)
The regulation of retail activities in Emilia Romagna Region has been characterized by three main phases. The first one starts with the approval of an Act in 1971, which aimed at supporting local authorities to realize and implement “plans” for the development of the retail local networks. The second one is related to the attempt of regulating the commercial development with programs and plans concerning aggregations of municipalities, after considering the poor effect of the regulation at the local level. During the third phase, starting with the reform of retail activities in 1998, the governance of commercial activities becomes mainly a concern of the large-scale plans, first of the Piani Territoriali di Coordinamento Provinciale (PTCP), realized and implemented by the Provincie.